Randai as a Social Representation Minangkabau Society of the Past - Indrayuda Indrayuda; Marzam Marzam; Mohd. Effindi Samsudin (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
Randai Arts is a cultural heritage used by the Minangkabau community as an entertainment which is called Pamenan in Minangkabau language means game. This article will reveal the social representation of the Minangkabau people in the past through the Randai show. As part of traditional Minangkabau performance art, Randai is packaged in a comprehensive form of performance, including motion, music, literature, and theater. Usually the stories shown are about the life stories of people from the past Minangkabau community. This research is a qualitative research using ethnographic and descriptive methods. Informants were selected using the purposive sampling technique, and used complementary instruments namely interview and observation guidelines. Data was collected through interviews, direct observation, and literature studies, as well as documentation studies. The analysis was carried out by adopting ethnographic methods, namely: (1) determining the object of study; (2) conducting domain analysis; (3) conducting taxonomic analysis; (4) conducting part analysis; (5) analyzing cultural themes; and (6) interpreting and concluding. The results of the research revealed that the art of Randai has never presented a story outside of humanitarian issues, namely the story of the social problems of the Minangkabau people of the past until now. This social problem is caused by social crises that often occurred in the past, in social life in Minangkabau. The problem revolves around love, household, and social status. To be cultural learning for the audience, the social issues in the past are brought up again in the story that is delivered in the Randai show.